COMMUNITY ATTITUDES AND PERCEPTIONS TOWARDS CLEAN WATER SUPPLY SYSTEMS AFTER THE EARTHQUAKE DISASTER (CASE STUDY OF WANGUNJAYA VILLAGE, CIANJUR DISTRICT) - Harsetya Adyatama, Bevan
Wangunjaya Village is one of the villages in Cugenang Sub-district, Cianjur Regency, which was hit by an earthquake. This research was conducted as part of the evaluation of clean water supply assistance that has been provided by the Institute for Research and Community Service (LPPM) ITB in the form of a mobile water treatment plant (IPA). This mobile water treatment plant provides clean water for the community in the evacuation center as well as the community in Wangunjaya Village. In evaluating the clean water distribution network and knowing the community's perception of clean water supply in Wangunjaya Village with the application of Theory of Planned Behavior. Quantitative methods were used with an offline questionnaire research instrument. And also to evaluate the provision of clean water before the earthquake, after the earthquake and the recovery period. The results showed that the distribution network did not yet have a transmission system and distribution system, with the water distribution discharge (6.53 l/sec) not sufficient to meet the water needs of the Wangunjaya Village population (7.88 l/sec). Respondents' knowledge of clean water was categorized as sufficient, with an average correct answer of 74.08%. Based on the regression results, the variables that have a positive relationship with the intention to use clean water are subjective norm, perceived behavioral control, and attitude (significance < 0.05) while the knowledge variable does not have a significant effect (significance > 0.05).